The Role of Electronic Word of Mouth and Destination Image in Shaping Tourist Visit Intention and Decision : A Case Study of Sebalang Beach, South Lampung - Nico Andreas; Roslina Roslina; Driya Wiryawan; Angga Febrian; Nuzul Inas Nabila; Adulai Sadjo Baldé Coordenador (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study analyzes the influence of Electronic Word of Mouth (eWOM) and destination image on visit intention and decision to Sebalang Beach, South Lampung. With tourists increasingly relying on online reviews, understanding these relationships is essential for effective destination marketing. The research addresses the issue of how eWOM and destination image affect tourists' decisions, aiming to provide insights for tourism stakeholders. A quantitative approach was used, employing a survey method with purposive sampling of 110 respondents who have visited or intended to visit Sebalang Beach. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test the proposed hypotheses. Findings indicate that destination image significantly influences visit intention and visit decisions, while visit intention also mediates the effect of destination image on visit decisions. However, eWOM does not have a significant impact on visit intention or visit decisions, and visit intention does not mediate the relationship between eWOM and visit decisions. These results suggest the importance of strengthening online promotional strategies and enhancing the positive image of Sebalang Beach. Encouraging content creation on social media and collaborating with influencers can effectively increase engagement and attract visitors. This study offers practical recommendations for tourism stakeholders to optimize Sebalang Beach’s potential and enhance its competitiveness as a tourist destination.